IMPLEMENTASI KEBIJAKAN PENGELOLAAN TATA RUANG WILAYAH KONSERVASI DAN PARIWISATA - Nerustia, Arinda Novpika; Rahmawati, Rita; Hernawan, Denny (JURNAL GOVERNANSI, 2015)
Puncak region Bogor as buffer capital Jakarta was being problem that was not easily resolved by all the competent authorities. Factor of natural damage caused by use of conservation land in an uncontrolled made the field and land space in the area threatens the abrasion of land surrounding hills. Puncak region Bogor was a part of an exclusive area that had room in its utilization. One of them was about the expansion of settlements to get the occupancy requirement level. However, this pattern should be observed not as the freedom to utilize space in the region, but the construction was systematically measured and targeted so as not to alter the pattern of the region of space become corrupted and no longer serves as a buffer area around it.Edward III stated that to measure the success of a policy implementation could be measured through the four basic variables of the communication; sources: disposition or attitude of the executive and bureaucratic structure.Implementation of spatial management policies in the Cisarua district referred to the existing regulations. This research examined two sources of policy implementation in Cisarua district in which Presidential Regulation Number 54, 2008 on National Strategic Planning Region Jakarta, Bogor, Depok, Tangerang, Jakarta, Puncak, Cianjur (Jabodetabekpuncur), and Regulation of Bogor District No. 19 of 2008 Concerning the Spatial Plan Bogor regency 2005-2025. Misuse of land, because its permit was easy from Buildings Licensing Agency, but supervision was not done from the agency concerned. This, which was perceived by the technical implementation in the field, which lack the resources and authority possessed limited.From this research was concluded that the element of implementing the policy and resources were still relatively minimal.